Ability Analysis of Pedagogical Content Knowledge of Prospective Teacher Students Majoring in Mathematics - Ruslan; Sahid; Pratiwi, Nurul Ilmi (EduLine: Journal of Education and Learning Innovation, 2022)
This research is qualitative research that aims to determine the Pedagogical Content Knowledge of prospective teacher students majoring in mathematics at the State University of Makassar. The research subjects consisted of 3 student-teacher candidates majoring in mathematics in the sixth semester. The subject-taking technique in this study amounted to three student teacher candidates majoring in mathematics with a cumulative achievement index of less than 3.00 and 3.01 - 3.50 and 3.51 - 4.00. The instruments in this study used CoRe, PaP-eRs, and Vignette. Data collection techniques in this study are observations based on PCK indicators and giving the Vignette test. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and conclusions. Based on the results of the study, it shows that the pedagogical knowledge aspects of most of the points in CoRe are fulfilled. Then for the content knowledge aspect, the subject with an achievement index of 3.50 – 4.00 is at level 1, an achievement index of 3.00 – 3.50 is at level 0 and an achievement index of less than 3.00 is at level 2.